On the 2019 Business Roundtable “Statement on the Purpose of a Corporation” - Harrison, Jeffrey S.; Phillips, Robert A.; Freeman, R. Edward (Journal of Management, 2020)
The Business Roundtable, a large group of top CEOs, recently issued a statement defining the purpose of the corporation in stakeholder terms, a direct and intended reversal from an earlier statement that defined the duty of directors as serving the interests of stockholders. In this editorial, we briefly describe the major twists and turns in the stockholders-versus-stakeholders debate that make this statement so significant to management theory and practice. We then describe the implications of the statement for scholars and practicing managers. We end with a description of three specific research topics that require more research in light of this statement: firm boundaries, the nature of value creation systems, and theory regarding the destruction of stakeholder value.